2006
DOI: 10.1016/j.jmaa.2005.11.069
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Hilbert's inequality

Abstract: In this paper we make some further extensions of discrete Hilbert's inequality by using Euler-Maclaurin summation formula. We give the improvements of some previously obtained results and also compare our results with some previously known from the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 6 publications
2
69
0
Order By: Relevance
“…In this section, we first improve the result of [7,Lemma 2] by showing that inequality (1.4) is valid for any s > 2 when λ = 1. We then deduce that lim n→∞ f s (n) = 0.…”
Section: Further Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this section, we first improve the result of [7,Lemma 2] by showing that inequality (1.4) is valid for any s > 2 when λ = 1. We then deduce that lim n→∞ f s (n) = 0.…”
Section: Further Discussionmentioning
confidence: 83%
“…We note that the above inequality is valid when λ < 0 by the integral test. In [7,Lemma 2], it is shown that the above inequality is valid when 0 < s ≤ 2, −1 < λ < s−1 and 2 < s ≤ 14, −1 < λ ≤ 1. In the next section, we extend this result to the case of 1 < λ ≤ 2, λ + 1 < s ≤ 5 to prove the following…”
Section: Introductionmentioning
confidence: 99%
“…When K(m, n) = (m κ + n κ ) −λ , the kernel function is homogeneous of order −λ · κ. Specifying κ = λ = 1 we get Hilbert's expression in (1), while κ = 1 leads us to Yang's result (2). Assuming the homogeneity of K(·,·) and using non-conjugate Hölder pairs (p, q), p > 1, p −1 + q −1 1 we arrive at the classical Hilbert's double series theorems by Levin [5], Bonsall [1] and the recent ones by Krnić and Pečarić [4]. (We point out that the best constant problem is still open when p, q are not conjugated.…”
Section: Introductionmentioning
confidence: 83%
“…The range of the parameter λ ∈ (2 − min{p, q}, 2] in Yang's result (2) was enlarged (by new consequent parametrizations) to λ ∈ (0, 14] by Krnić and Pečarić, see [4,Theorems 1,2] in the conjugate, and [4, Theorem 4] for non-conjugate Hölder couple p, q. Therefore, the range of r in Theorem 1 can be enlarged as well.…”
Section: Final Remarksmentioning
confidence: 98%
See 1 more Smart Citation